2018
DOI: 10.1039/c8sc01798k
|View full text |Cite
|
Sign up to set email alerts
|

Norbornene chaotropic salts as low molecular mass ionic organogelators (LMIOGs)

Abstract: A humble norbornene functions as an ionic organogelator, forms aqueous biphasic and triphasic systems and assembles to form chiral helices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Chiral LMWGs have proved to be an excellent class of soft materials ,, due to their potential applications in the field of asymmetric catalysis, chiral nanomaterials, and chiral recognition. Gel fibers often show chirality at a mesoscopic scale, which is evident from their morphology (helical cylinders or multiple helices), and Gunnlaugsson and Pfeffer’s group showed that chirality of the gelator dictates the self-assembly processes of gels resulting in the formation of helical materials . Chirality plays an important role in controlling and mediating the self-assembly of LMWGs, which clearly explains the occurrence of stereogenic centers ,,,, in most LMWGs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral LMWGs have proved to be an excellent class of soft materials ,, due to their potential applications in the field of asymmetric catalysis, chiral nanomaterials, and chiral recognition. Gel fibers often show chirality at a mesoscopic scale, which is evident from their morphology (helical cylinders or multiple helices), and Gunnlaugsson and Pfeffer’s group showed that chirality of the gelator dictates the self-assembly processes of gels resulting in the formation of helical materials . Chirality plays an important role in controlling and mediating the self-assembly of LMWGs, which clearly explains the occurrence of stereogenic centers ,,,, in most LMWGs.…”
Section: Introductionmentioning
confidence: 99%
“…Gel fibers often show chirality at a mesoscopic scale, which is evident from their morphology (helical cylinders or multiple helices), 48 and Gunnlaugsson and Pfeffer's group showed that chirality of the gelator dictates the self-assembly processes of gels resulting in the formation of helical materials. 51 Chirality plays an important role in controlling and mediating the self-assembly of LMWGs, which clearly explains the occurrence of stereogenic centers 14,43,48,49,52 in most LMWGs. LMWGs based on enantiomerically pure chiral molecules display strong gelling ability compared to their racemates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This approach was used by Pfeffer and co-workers to explain the gelation behavior of the enantiomers compared to the nongelator racemate. 72 However, the analysis of the self-assembly process in multicomponent gels based on enantiomers using SCXRD is not reported till date because of the lack of crystal structures of all possible stereoisomeric forms and the mixed enantiomers. The combination of single-crystal X-ray structure of the gelator and powder diffraction pattern of either the native gel or the xerogel will enable us to correlate the intermolecular interactions observed in the single-crystal structure with the molecular aggregation in the gel state.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Single-crystal X-ray diffraction (SCXRD) has been used to identify the key interactions in the solid-state structure of LMWGs, which may provide some insight into the packing modes of these molecules in gel fibers. This approach was used by Pfeffer and co-workers to explain the gelation behavior of the enantiomers compared to the nongelator racemate . However, the analysis of the self-assembly process in multicomponent gels based on enantiomers using SCXRD is not reported till date because of the lack of crystal structures of all possible stereoisomeric forms and the mixed enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, fully transparent gels (Fig. 2) for perfluoromethylcyclohexane (PFMC, bp 76 °C, d 1.79 g/cm 3 ), perfluorodecalin (PFD, bp 142 °C, d 1.92 g/cm 3 ) and perfluorotripentylamine (FC-70, bp 215 °C, d 1.93 g/cm 3 ) containing as little as 0.5-0.6 wt% of 1 for PFD and PFMC, and 1 wt% for FC-70, were obtained. These weight fractions correspond to the lowest gelation concentrations of 9.5 mM and 17 mM, respectively.…”
mentioning
confidence: 99%